2023
DOI: 10.1186/s40851-023-00203-y
|View full text |Cite
|
Sign up to set email alerts
|

Coelomocytes of the Oligochaeta earthworm Lumbricus terrestris (Linnaeus, 1758) as evolutionary key of defense: a morphological study

Abstract: Metazoans have several mechanisms of internal defense for their survival. The internal defense system evolved alongside the organisms. Annelidae have circulating coelomocytes that perform functions comparable to the phagocytic immune cells of vertebrates. Several studies have shown that these cells are involved in phagocytosis, opsonization, and pathogen recognition processes. Like vertebrate macrophages, these circulating cells that permeate organs from the coelomic cavity capture or encapsulate pathogens, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Consistent with previous studies [35], hemocytes show a co-localization of immunoreactivity signals for TLR2 and iNOS. In previous studies, we demonstrated that the presence of different molecules may be related to a different cellular function [35,38]. In this study, not all hemocytes colocalized for the antibodies tested, suggesting a diversification between phagocytic hemocytes that bind TLR2 and cytotoxic hemocytes presenting only iNOS.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Consistent with previous studies [35], hemocytes show a co-localization of immunoreactivity signals for TLR2 and iNOS. In previous studies, we demonstrated that the presence of different molecules may be related to a different cellular function [35,38]. In this study, not all hemocytes colocalized for the antibodies tested, suggesting a diversification between phagocytic hemocytes that bind TLR2 and cytotoxic hemocytes presenting only iNOS.…”
Section: Discussionmentioning
confidence: 45%
“…However, a similar number of membrane-bound receptors have been found in other deuterostomes and protostomes, including the Pacific oyster C. gigas [50]. In previous studies, we evaluated TLR2 presence in several metazoans: mollusks bivalves Polititapes aureus (Gmelin, 1791), Cerastoderma glaucum (Bruguière, 1789) [51], and Mytilus galloprovincialis (Lamarck, 1819) [52]; annelida Lumbricus terrestris (Linnaeus, 1758) [38]; protochordate tunicate Styela plicata (Lesuer, 1823) [53]; chordates cyclostomes Eptatretus cirrhatus (Forster, 1801) [54]; chondrichthyes Scyliorhinus canicula (Linnaeus, 1758) [55]; chordates osteichthyes Carassius auratus auratus (Linnaeus, 1758) [56], Polypterus senegalus (Cuvier, 1829), Lepisosteus oculatus (Winchell, 1864), Clarias batrachus (Linnaeus, 1758) [57], Periophthalmodon schlosseri (Pallas, 1770) [58], and Danio rerio (Hamilton, 1822) [59]; and in the marine mammal Stenella coeruleoalba (Meyen, 1833) [60]. TLR can be found in hemocytes more than in other tissues, and its transcription is significantly upregulated in bacterial and viral infections.…”
Section: Discussionmentioning
confidence: 95%
“…In the group exposed to both pollutants, a significant increase in hemocytes was noted, suggesting a synergistic effect of the two compounds on defense cells. Moreover, interestingly, not all hemocytes colocalized for the antibodies tested, suggesting that hemocytes positive for iNOS might also have a cytotoxic function, while those positive only for TLR2 might perform a mostly phagocytic function, as reported in previous studies [ 71 , 72 ]. Furthermore, TLR2- and iNOS-positive epithelial cells were found in pollutant-exposed groups, suggesting an involvement of these cells in oxidative stress-induced responses.…”
Section: Discussionmentioning
confidence: 53%
“…Toll-like receptors (TLRs) are a class of phylogenetically highly conserved transmembrane proteins that play an important role in the innate immune system by recognizing pathogen-associated molecular patterns (PAMPs) and initiating immune responses [ 67 , 68 , 69 , 70 ]. We previously demonstrated TLR2 expression in the defense cells of invertebrates [ 71 , 72 ], protochordates [ 73 , 74 ], and several aquatic vertebrates such as myxins [ 74 , 75 ], cartilaginous fish [ 76 ], and bony fish [ 77 , 78 , 79 ]. Inducible nitric oxide synthase (iNOS) is an enzyme that catalyzes the production of nitric oxide (NO) in response to various stimuli, such as pathogens and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Its epidermis performs various functions, including calcium transport, respiration, feeding and defence. It consists of a columnar pseudostratified epithelium with supporting, basal, glandular and sensory cells, covered by an overlying fibrous cuticle (Alesci, Capillo, et al, 2023). Epidermal glandular cells are mucous or protein‐like with secretory activities (Coggeshall, 1966).…”
Section: Introductionmentioning
confidence: 99%